The Effect of Sanyinjiao Point (SP6) Acupressure on the Dysmenorrhea Pain Scale at SMP N 4 Kotamobagu - Stery Sindy Pelealu; Raden Maria Veronika Widiatrilupi; Anik Purwati (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Dysmenorrhea or menstrual pain is a common complaint in adolescent girls that can interfere with daily activities. One method that can be used to reduce menstrual pain is acupressure, especially at the Sanyinjiao point (SP6), which is known to relieve dysmenorrhea symptoms. This study aims to determine the effect of acupressure at the Sanyinjiao point (SP6) on reducing the scale of dysmenorrhea pain in students of SMP N 4 Kotamobagu. This type of research is quantitative with a pre-post test experimental design. A total of 18 respondents were selected by purposive sampling. This study used a pain scale measuring instrument to assess the level of dysmenorrhea pain before and after acupressure treatment was given at the Sanyinjiao point (SP6). Based on the results of statistical analysis, the p-value obtained was 0.001, which indicates a significant effect between acupressure at the Sanyinjiao point (SP6) on reducing the scale of dysmenorrhea pain in respondents. Acupressure at the Sanyinjiao point (SP6) has been proven effective in reducing the pain scale of dysmenorrhea in female adolescents at SMP N 4 Kotamobagu. It is recommended that acupressure can be applied as a non-pharmacological method in overcoming menstrual pain in female adolescents